Peruvian archaeology : a critical history - Tantaleán, Henry, 1974- (Walnut Creek, California : Left Coast Press, 2014)
"This book offers a unique, critical perspective on the history of Peruvian archaeology by a native scholar. Leading Peruvian archaeologist Henry Tantalean illuminates the cultural legacy of colonialism beginning with "founding father" Max Uhle and traces key developments to the present. These include the growth of Peruvian institutions; major figures from Tello and Valcarcel to Larco, Rowe, and Murra; war, political upheaval, and Peruvian regimes; developments in archaeological and social science theory as they impacted Andean archaeology; and modern concerns such as heritage, neoliberalism, and privatization. This post-colonial perspective on research and its sociopolitical context is an essential contribution to Andean archaeology and the growing international dialogue on the history of archaeology"--
Introduction : The crisscrossed past -- The beginnings of archaeology in Peru -- The foundation (Western) of Peruvian archaeology : Max Uhle and cultural evolutionism -- Archaeology and nationalism in the 1920s : Julio C. Tello and Peruvian culture -- Indigenismo in the ancient capital of the Incas : the Cusqueno period of Luis Valcarcel -- North American influence in the 1940s : Rafael Larco Hoyle and the Viru Project -- New horizons in Peruvian archaeology : John H. Rowe and the Berkeley School -- Ethnohistory and archaeology in the 1960s : John Murra's influence in Peru -- Archaeology as social science : from Gordon Childe to Luis Lumbreras -- Processualist archaeology in Peru : emergence and development -- Archaeology in 1990s Peru : a view from Lima -- Peruvian archaeology at the beginning of the twenty-first century : boom and bust -- Conclusion : New horizons for Peruvian archaeology in a globalized world.
Includes bibliographical references (pages 171-196) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Archaeology -- Peru -- History; Excavations (Archaeology) -- Peru -- History; Archaeological expeditions -- Peru -- History; Peru; Electronic books